Tenax-GC Extraction Technique for Residual Polychlorinated Biphenyl and Polyaromatic Hydrocarbon Analysis in Biodegradation Assays - Shiaris, M. P. (1980)
A rapid Tenax-GC extraction technique has been evaluated for use in conjunction with aqueous biodegradation assays for polyaromatic hydrocarbons and polychlorinated biphenyls. The method was quantitatively efficient and reproducible for phenanthrene, but variable and not quantitative for Aroclor 1254 (polychlorinated biphenyls). Aqueous sample volumes and varying concentrations of organic matter influenced polychlorinated biphenyl and polyaromatic hydrocarbon extraction efficiency. Phenanthrene recovery was decreased by soil extract but unaffected by spent bacteriological culture medium. Both types of organic matter caused significant reduction of Aroclor 1254 recovery. Polyaromatic hydrocarbon and polychlorinated biphenyl biodegradation assays, performed with reservoir samples, supported the laboratory evaluation. The study demonstrated the utility of the Tenax-GC extraction technique for phenanthrene analysis in biodegradation assessment; however, Tenax-GC extraction was not appropriate for Aroclor 1254 biodegradation studies.